The Impact Of Intra-Firm Sourcing Strategy And Inter-Firm Sourcing Strategy On Supplies' Quality, Delivery And Cost - Khaw, Phaik Lean (1999)
In recent years, the business environment has become intensely competitive. Firms, searching for sources of competitive advantage begin to look into the potential of sourcing in adding value as purchased inputs account for 60% to 80% of cost of goods sold. Thus, the objective of this research paper is to investigate which sourcing strategy, intra-firm or inter-fiRn, will lead to better supplies' quality, delivery and cost and whether in the process of achieving this outcome, it is moderated by environmentrelated factors.